EVALUASI KELONGSORAN DAN ALTERNATIF PERKUATAN MENGGUNAKAN GEOTEKSTIL DENGAN PROGRAM GEOSLOPE (STUDI KASUS: KELONGSORAN TOL CIPALI KM 122 JALUR B) - Akhdan Fajri Ramadan; Putera Agung Maha Agung (Construction and Material Journal, 2022)
Reinforcement of a slope is a step that is often taken in increasing the Safety Factor (SF) of an embankment or excavation. In the road toll Cikopo - Palimanan the road which discount a lot of excavation and heap case the resulted in the magnitude of the possibility landslide. This studies to evaluate about handling of a landslide STA on the road toll Cikopo - Palimanan namely at KM 122 + 600 Line B here reinforcement sed is Geotextile. The analysis is used in calculating the Safety Factor (SF) manually or using a program Geoslope using methods Bishop where the field of landslide divided into several segments to be calculated force that worked in the segments from the analysis manually without the influence of the earthquake number of safeties is 1.6 and by using the program the result is 1.5. For analysis is with the influence of the earthquake (kh) of 0,2 obtained the numbers of safety 1.05 using manual analysis and 0.9 using the program. From these results, the slope without reinforcement with the influence of the earthquake must be strengthened because SF 1.10. Reinforcement using geotextiles is divided into 2 because the embankment height is > 6 meters, namely the lower zone and the upper zone, with the distance between the geotextile and the length of the geotextile being the lower zone of 0.30 m and 30 m, while for the upper zone the distance between the geotextile and the length of the geotextile is 0. 60 m and 18.5 m. From the results of the geotextile use as reinforcement have Safety Factor score at 1.49 which increased by 40% from the condition without reinforcement  Keywords: Geotextile, Landslide, Reinforcement, Safety Factor.